Contribution of Understanding Design Principles and Control of Design Media Use on Aesthetic Quality Design Students of Fashion Vocational School in Kudus - Puspita, Rahma Aditia; Wahyuningsih, Sri Endah; Syamwil, Rodia (Universitas Negeri Semarang, 2018)
Understanding the basic material of design and mastery of the media if it is technically adequate, it can be ascertained that the design of the clothes produced by students looks more aesthetic.Â The purpose of research:Â (1)Â determine theÂ contribution of understanding of the design principles of the aesthetic quality fashion design,Â (2)Â determineÂ contributions mastery media use design to the aesthetic quality of fashion design,Â (3)Â determine contributions jointly between the understanding of design principles and mastering the use of design media for the aesthetic quality of fashion designs made by fashion students of Vocational School in Kudus.Â The pattern used in this study is correlation with a quantitative approach.Â The studiesÂ population is 76 second grade studentÂ of dressmaking study program ofÂ SMK N 1Â Kudus.Â The research sample isÂ 38 studentsÂ inclass XIÂ TBÂ 1 SMK N 1 Kudus.Â In this studyÂ there are 2 independent variablesÂ namelyÂ Understanding the Principles of DesignandÂ Mastery of Use of Media Design.Â MeanwhileÂ the dependent variable isÂ Aesthetic Quality Design. InÂ doingÂ validation, there are 2 ways, namely:Â (1)Â Expert ValidationÂ (2)Â Trial Validation.Â ReliabilitasÂ itemsÂ madeÂ by using AlphaÂ formula.Â The data analysis technique uses theÂ correlationÂ analysis formula.Â ReliabilityÂ performen this studyÂ using aÂ test of consistency cohen's kappa.Â There contributed between 1st assessors and 2nd assessors on the aesthetic quality of design with koefiseincohen's kappa value of 0.200Â which means there is no agreement among 1st assessors and 2ndassessors in assessing the aesthetic quality fashion design.Â The results showed that based onÂ calculationsÂ Ï€ x1y.x = 0,296, dan Ï = 0,040 Ë‚ 0,05 which indicates that it is significant, supported by data (accepted). The values obtained showÂ an understanding of design principlescontributing positively toÂ the aesthetic quality of fashion designs.Based onÂ calculations Ï€ x2y.x1 = 0,808, Ï = 0,00 Ë‚ 0,05 which indicates that it is significant, supported by data (accepted).Â The value obtained showsÂ mastery of the use of design mediaÂ contributes positively toÂ the aesthetic quality of fashion designs.Â Based on the calculation of the correlation test in the third hypothesis, R = 0.989, with FcountÂ = 732,482, and Ï = 0,00 Ë‚ 0,05, thus the correlation coefficient is positive, the relationship is in the same direction between the two variables.Â That is, there is a positive relationship between understanding the principles of design and the use of media with the aesthetic quality of fashion designs.Â After comparing it with a table, it is concluded that it has aÂ very highÂ correlation.Â This implies that the influence of the independent variable (X) on the dependent variable (Y) isÂ 97,8Â %, the rest is influenced by other variables.